1999
DOI: 10.1097/00000658-199902000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Recurrence After Curative Resection of Hepatocellular Carcinoma

Abstract: Aggressive treatment with a multimodality strategy could result in prolonged survival in patients with intrahepatic recurrence after curative resection for HCC. Prognosis was determined by the liver function status, interval to recurrence, number of recurrent tumors, any concurrent extrahepatic recurrence, and type of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
436
3
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 533 publications
(458 citation statements)
references
References 29 publications
13
436
3
6
Order By: Relevance
“…As vascular invasion frequently occurs in HCC and often predicts tumor invasion and metastasis (Poon et al, 1999), our finding may be interpreted as PFTK1 overexpressions that correlate with a more aggressive tumor phenotype. We also obtained functional evidence showing the mechanistic action of PFTK1 protein kinase through an intermediate substrate TAGLN2.…”
Section: Discussionmentioning
confidence: 67%
“…As vascular invasion frequently occurs in HCC and often predicts tumor invasion and metastasis (Poon et al, 1999), our finding may be interpreted as PFTK1 overexpressions that correlate with a more aggressive tumor phenotype. We also obtained functional evidence showing the mechanistic action of PFTK1 protein kinase through an intermediate substrate TAGLN2.…”
Section: Discussionmentioning
confidence: 67%
“…26 Portal vein thrombosis had been found to be a poor prognostic variable in multiple studies. 27 Microscopic and macroscopic portal vein involvement is one of the major modes of spread of HCC, leading to recurrence after resection 28 and transplantation. 29 In addition, portal venous thrombosis can lead to complications of portal hypertension such as ascites, variceal hemorrhage, and worsening hepatic function in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several individual small trials that have demonstrated potential benefit of some adjuvant therapies, evidence from such trials is weak and there is no well-proven effective adjuvant treatment to prevent recurrence so far [263]. Aggressive management of tumor recurrence by repeat resection, ablation, or transarterial chemoembolization (TACE) is currently the most practical way to prolong patient survival [263,264].…”
Section: Liver Resectionmentioning
confidence: 99%